Optimized behavior of long-term rainfall for the red sea semi-arid region - Aldrees A.; Taha A.T.B.; Alqahtani A.; Hayder G. (Techno-Press, 2023)
Agriculture; Catchments; Digital storage; Seawater; Water resources; Annual rainfall; Impact on the environment; Khor arbaat; Long-term rainfall analyse; Monthly rainfalls; Rainfall analysis; Red sea; Semi-arid region; Significant variables; Waters resources; Rain